Biomolecular Structure and Dynamics with Neutrons: The View from Simulation. Issue 8 (31st July 2014) - Hong, Liang; Petridis, Loukas; Smith, Jeremy C.
Abstract The characterization of the structure and internal dynamics of biomolecules is essential to understanding their biological function. Neutron scattering probes similar time‐ and length‐scales to molecular dynamics simulation. Hence, simulation models of biomolecules have become invaluable in the interpretation of experimental neutron data. Here, we report on advances in the application of simulation in developing neutron scattering to investigate internal protein motions and, as an example of industrial relevance, in the derivation of physical models of use in biofuel renewable energy research.